Paleozoic Geodynamics and Architecture of the Southern Part of the Mongolian Altai Zone. Issue 8 (26th August 2022) - Sukhbaatar, T.; Lexa, O.; Schulmann, K.; Aguilar, C.; Štípská, P.; Wong, J.; Jiang, Y.; Míková, J.; Zhao, D.
Abstract: The Mongolian Altai Zone of the Central Asian Orogenic Belt has been traditionally interpreted as a mosaic of Paleozoic magmatic arcs, back‐arcs, and Precambrian continental terranes. In order to define its architecture and its tectonic evolution, three domains previously interpreted as terranes were investigated. The findings show that the Northern and Central domains are formed by a metamorphic sequence characterized by Barrovian S1 fabric transposed by recumbent folds and dominant sub‐horizontal amphibolite facies S2 schistosity. The latter is associated with the intrusions of late Devonian syntectonic granite sheets and anatexis in the south. The Southern domain is formed by early Permian migmatites and anatectic granites separated from the metamorphic envelope by amphibolite to green‐schist facies D3 shear zone cross‐cutting S2 fabrics. All domains have been reworked by E‐W upright folds associated with axial‐planar greenschist facies cleavage, reflecting the final mid‐Permian to Triassic D4 shortening. Lithological, geochemical, and U‐Pb zircon analyses of metasediments of all domains indicate that they are formed by Ordovician mature quartzite derived from Precambrian basement intruded by Cambrian‐Ordovician continental arc and Silurian immature graywacke which originated through erosion of an oceanic arc. Altogether, the whole sequence represents a fore‐arc basin in front of a migrating arc affected by thickening and late Devonian extension. The Southern domain is interpreted as an early Permian core complex amplified by mid‐Permian to Triassic compression. The apparent "terrane" architecture of the Mongol Altai Zone originated due to Devonian and Permian heterogeneous reworking of a giant Ordovician to Silurian fore‐arc basin. Key Points: The Mongolian Altai Zone is an Ordovician to Silurian fore‐arc basin affected by Barrovian prograde metamorphism Late Devonian extension resulted in intrusion of sub‐horizontal, syntectonic granite sheets and partial melting in deep crustal levels Early Permian extension resulted in the formation of metamorphic core complex later amplified by regional mid‐Permian to Triassic compression